The Core Principles of Islamic Jurisprudence within Legal Theory: A Comprehensive Analysis - Faizi, Hafiz Falak Shair; Ali, Dr. Hafiz Sfarish (Online Journal of Research in Islamic Studies, 2024)
This article provides a comprehensive analysis of the core principles of Islamic jurisprudence within the framework of Islamic legal theory (Usūl al-Fiqh). It delves into the foundational sources of Islamic law—Qur’ān, Sunnah, Ijmā’, and Qiyās—examining their roles and interrelationships in shaping legal thought and practice. The study explores the evolution of these principles through historical contexts and the development of major schools of thought, including Hanafi, Maliki, Shafi’i, and Hanbali, highlighting their unique contributions to Islamic jurisprudence. Furthermore, the article discusses methodologies such as Ijtihād (independent reasoning) and Taqlid (imitation), assessing their significance in both historical and contemporary settings. A comparative analysis with Western legal theories underscores the distinct yet occasionally intersecting paths of Islamic and Western legal traditions. The relevance of Islamic jurisprudence in modern legal systems, particularly in Muslim-majority countries, is critically examined, considering challenges and opportunities in integrating traditional principles with contemporary legal frameworks. Through case studies and practical applications, the article demonstrates the enduring impact and adaptability of Islamic legal principles. It addresses internal debates and external criticisms, providing a balanced perspective on the strengths and limitations of Islamic jurisprudence. Ultimately, this study underscores the importance of understanding Islamic legal theory’s foundational principles to appreciate its role and potential in the global legal landscape.